Problematika Siswa dalam Proses Pembelajaran Mata Pelajaran Bahasa Arab di Kelas 5 Madrasah Ibtidaiyah Negeri (MIN) 01 Kota Bengkulu - Maryam Maryam; Sri Sundari; Citra Adelina; Randi Akbar; Fery Ramadhan (Al-Khair Journal: Management Education, 2025)
Abstract: Students still experience problems in the learning process of Arabic subjects, it can be seen that students are not interested in taking Arabic subjects. The purpose of this study is to map and analyze student problems in the learning process of Arabic subjects in grade 5 MIN 1 Bengkulu City. Using a descriptive qualitative method. The results of the study show that Arabic learning for class V MIN 1 Bengkulu City faces several problems. The most common problems encountered are that students are not interested in learning Arabic, do not master Arabic vocabulary, and have an environment that does not support students' learning progress, teachers are not able to explain the goals and benefits of learning Arabic, students do not have the desire and motivation to learn Arabic, madrassas do not provide opportunities and infrastructure to students to develop their Arabic language skills. So it can be concluded that the learning process of Arabic subjects is still experiencing problems for students, such as students are not interested, and students have no motivation to learn Arabic in madrassas.Keywords: Student Learning Problems, Arabic Language Subjects, Madrasah Ibtidaiyah Negeri (MIN) 01 Bengkulu City. Abstrak: Siswa masih mengalami problematika dalam proses pembelajaran mata pelajaran Bahasa Arab, terlihat siswa tidak tertarik mengikuti mata pelajaran Bahasa Arab. Tujuan penelitian ini untuk memetakan dan menganalisis problematika siswa dalam proses pembelajaran mata pelajaran Bahasa Arab di kelas 5 MIN 1 Kota Bengkulu. Menggunakan metode kualitatif deskriptif. Hasil penelitian menunjukkan bahwa pembelajaran bahasa Arab bagi kelas V MIN 1 Kota Bengkulu menghadapi beberapa problematika yaitu lingistik dan non linguistik. Problematika yang paling umum dijumpai adalah siswa tidak tertarik untuk belajar bahasa Arab, tidak menguasai kosa kata bahasa Arab, dan lingkungan tidak mendukung kemajuan siswa belajar, sebagian guru juga tidak mampu menjelaskan karakter siswa dan tujuan serta manfaat pembelajaran bahasa Arab, siswa tidak memiliki keinginan dan motivasi untuk belajar bahasa Arab, madrasah tidak memberikan kesempatan dan sarana prasarana kepada siswa untuk mengembangkan kemampuan berbahasa Arab mereka. Sehingga dapat disimpulkan bahwa proses pembelajaran mata pelajaran Bahasa Arab masih mengalami problematika bagi siswa, seperti siswa tidak tertarik, dan siswa tidak ada motivasi untuk belajar Bahasa Arab di madrasah.Kata kunci: Problematika Belajar Siswa, Mata Pelajaran Bahasa Arab, Madrasah Ibtidaiyah Negeri (MIN) 01 Kota Bengkulu.